Menyemah Kampung: Creating a Harmonic Life with the Sumatran Tiger - Rio Zulkarnain; Bambang Hariyadi; Agus Subagyo (Journal of Tropical Ethnobiology, 2022)
The Sumatran tiger is one of the keystone species increasingly under threat. Several traditional communities perceive the tiger has an essential role in a broader aspect of life; the animal constitutes an integral part of their culture. This study discusses the interaction between the traditional Malay community around the Kerumutan Wildlife Reserve (KWR) in Riau, Sumatra, and the Sumatran tigers. We collected data through in-depth interviews with several local traditional leaders recruited by snowball sampling. The local people around the wildlife reserve believed that the tiger is a sacred animal and thus should be protected. The community perceived that the animal has several roles in guarding their village against evils. To respect the presence of the tiger, people around the KWR performed a ritual of Menyemah Kampung once a year. However, many changes have been taking place that change nature and the people, including the Menyemah Kampung ritual. Local people’s perception changes toward the ritual may also affect the conservation of the Sumatran tiger.